Characterization and Quality Analysis of Puff Pastry Made with Corn-Based Dough - Anni Faridah; Juliana Siregar; Rahmi Holinesti; Ranggi Rahimul Insan; Wiwik Indrayeni; Fitriyasih Fitriyasih; Ade Raimuna (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
This study aimed to analyze the dough characteristics and quality of puff pastry with corn flour as a partial substitute for wheat flour. The use of local ingredients such as corn is important for supporting food diversification and developing healthier bakery products. An experimental method compared a control puff pastry made with 100% wheat flour and a formulation containing corn flour substitution. Samples were evaluated through microscopic observation, Scanning Electron Microscopy (SEM), and nutritional analysis. The results showed that corn flour substitution affected the properties of puff pastry. Microscopic observations indicated that the substituted product had higher porosity and less distinct layer formation than the control, especially on the first day after baking. During storage, the corn-based puff pastry exhibited an increase in hollow structures, indicating changes in internal morphology. SEM analysis confirmed differences in microstructure, with the control sample displaying smoother, clearly defined layers, whereas the substituted sample showed a more porous and irregular structure. Nutritional analysis revealed that corn substitution increased moisture, ash, and protein contents while decreasing fat and carbohydrate levels compared with the control. Overall, corn flour substitution influenced puff pastry texture and composition while demonstrating potential for developing nutritious bakery products from locally available ingredients